Kontrol Diri Wanita yang Menunda Pernikahan - Sabrina, Latifa Nur; , Aad Satria Permadi, S.Psi, MA (2016)
Delaying marriage is an act committed by individuals aged ≥25 years and older who set back the time for binding between two individuals into one to form a family. Delaying marriage done by women generally caused by the desire for a career, the freedom to make changes and mobility, and independence in psychologically and social. The purpose of this study is to understand and describe the self-control of women who delay marriage. This study uses a phenomenological qualitative research methods with informants were selected by purposive sampling The informants criteria is women aged ≥25 years age, have a relationship with the opposite sex, domiciled in the city of Surakarta, planning to get married and will perform marriages. Based on these criteria the researchers took 5 informants, 3 informants are the principal subject and 2 informants are the comparison subject. Based on the research done self-control in a woman who delay marriage is dynamic it was influenced by several factors including maturation, interpersonal relationships within the family, commitment, interaction and intimacy intensity, individual's personality and prejudice.